Establishment of pseuderanthemum palatiferum (nees) radlk callus culture and screening of secondary metabolite production - Petsangkrit N. (2017)
© 2016 The Authors. Published by Innovare Academic Sciences Pvt Ltd. Objective: This study aims to establish callus culture of Pseuderanthemum palatiferum and to investigate the production of secondary metabolites from callus extracts. Methods: Callus tissues were initiated using explants from in vitro, aseptically-grown plants. The effects of medium salt base (Murashige & Skoog; MS or Gamborg B5; GB5) and plant growth regulators (2,4-dichlorophenoxyacetic acid; 2,4-D, naphthaleneacetic acid; NAA, benzyl aminopurine; BAP) on the initiation of callus tissues were investigated. The growth of callus culture was studied, and an optimized medium was determined. The production of secondary metabolites in callus was investigated, in comparison with P. palatiferum leaf, on ethanolic extracts using test reagents and thin-layer chromatography (TLC). Results: The condition suitable for initiation of callus from leaf explant was MS salt bases, supplemented with 5.37 μM NAA, which yielded friable callus within 2 w. After transfer, best growth was observed in MS medium supplemented with 5.37 μM NAA and 0.44 μM BAP, after 4 w. Chemical screening and TLC analysis of callus extracts showed presences of some secondary metabolites similar to that of the leaf extract, together with additional phytochemicals not originally found in P. palatiferum plant. Conclusion: Callus culture was successfully established. With optimum culture conditions, this in vitro culture and can serve as another method to obtain medicinally-useful secondary compounds from P. palatiferum.